1999
DOI: 10.1115/1.2841231
|View full text |Cite
|
Sign up to set email alerts
|

A Shock Loss Model for Supersonic Compressor Cascades

Abstract: Loss models used in compression system performance prediction codes are often developed from the study of two-dimensional cascades. In this paper, compressible fluid mechanics has been applied to the changes in shock geometry that are known to occur with back pressure for unstarted operation of supersonic compressor cascades. This physics-based engineering shock loss model is applicable to cascades with arbitrary airfoil shapes. Predictions from the present method have been compared to measurements and Navier–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Recent investigations (Konig et al [18,19], Bloch [20]) have shown that the efficiency characteristic of high ( 1)…”
Section: Total Pressure Lossmentioning
confidence: 98%
“…Recent investigations (Konig et al [18,19], Bloch [20]) have shown that the efficiency characteristic of high ( 1)…”
Section: Total Pressure Lossmentioning
confidence: 98%
“…Once again, the major drawbacks of this method are that it gives wrong predictions for lower Mach numbers and that the shock formulas which are used in it are very sensitive. This is maybe one of the reasons why Bloch et al [12] had to take into account an "effective" leading edge radius in their model dedicated to predict the shock loss through the lower branch of Moeckel's hyperbola, in supersonic compressor cascades operating in unstarted regime. Indeed, they increased the leading edge thickness until the analytical results matched the experimental ones.…”
Section: Shock Loss Predictionmentioning
confidence: 99%
“…[10,11], for example. Bloch, Copenhaver and O'Brien also give an interesting approach based on Moeckel's method [12], adapted to unstarted regime.…”
Section: Shock Loss Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weekly luncheons, occasional "turoboguys' nite out," and other get-togethers provided welcome relief from academic woes. (Konig, et al, 1996) .... (Bloch, et al, 1999).......... (Billet, et al, 1988) (Hah, et al, 1998) (Miller, et al, 1961)....... Figure 3 -4 Contours of tip relative total pressure loss coefficient near rotor trailing edge (Lakshminarayana, et al, 1985). (NASA SP-36, 1965) ............................................................................................................…”
mentioning
confidence: 99%